2010
DOI: 10.1055/s-0030-1249052
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic Resection of Lumbar Discal Cysts

Abstract: Microendoscopic resection appears to be a minimally invasive and feasible surgical option for the treatment of lumbar discal cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…7) Seven cases of discal cyst were treated by minimal invasive surgical resection using microendoscopy. 10) Only two cases of discal cyst were treated conservatively and regressed as confirmed by MR imaging. 3,5) The first case of``disc cyst'' with imaging-confirmed regression and symptomatic relief without surgery was reported in 2001, but whether any other type of medical intervention was administered is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…7) Seven cases of discal cyst were treated by minimal invasive surgical resection using microendoscopy. 10) Only two cases of discal cyst were treated conservatively and regressed as confirmed by MR imaging. 3,5) The first case of``disc cyst'' with imaging-confirmed regression and symptomatic relief without surgery was reported in 2001, but whether any other type of medical intervention was administered is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Various randomized and nonrandomized trials have shown that MED is less invasive than conventional discectomy, [2][3][4][5][6] and microendoscopic approaches have also been applied in the treatment of other lumbar diseases, including spinal canal stenosis, 7 extraforaminal stenosis, 8 apophyseal separation, 9 and intraspinal cystic lesions. 10,11 However, several studies report complications with MED, such as dural tears and a higher rate of recurrence than after conventional discectomy. 12,13 In particular, the risk of recurrence may sometimes outweigh the advantage of a minimally invasive treatment, because patients experience recurrent pain and can require additional conservative and/or surgical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Microsurgical resection of the cyst is recommended treatment, as is reported in the majority of published cases. [ 4 10 11 12 ] Removal of the corresponding disc along with the cyst, however, also remains controversial. [ 11 ] We did not perform discectomy in our patient and removed only the subligamentously herniated portion of the disc, which was directly communicating with the cyst.…”
Section: Discussionmentioning
confidence: 99%